3D‐Printed, High‐Porosity, High‐Strength Graphite Aerogel. Issue 7 (16th June 2021) - Liu, Dapeng; Chen, Chaoji; Zhou, Yubing; Bao, Yinhua; Wang, Ruiliu; Liu, Yu; He, Shuaiming; Huang, Hao; Zhang, Clark; Foster, Bob; Li, Teng; Hu, Liangbing
Abstract: The global demand for plastic foam materials is enormous (annual worth of ≈341.3 billion) and still surging with an annual growth rate of 4.8%, driven by increasing modern societal needs. The majority of existing foam materials are made of plastics, which take hundreds of years to degrade, leading to severe global pollution issues. Here, a degradable, recyclable, and cost‐effective solution to foam materials based on 3D graphite‐cellulose nanofibers (G‐CNF) foam fabricated from resource‐abundant graphite and cellulose via advanced 3D printing is reported. The CNFs can directly disperse the graphite under physical sonication without the need for any chemical reactions. The interaction of the CNFs with graphite through the function of hydrophilic and hydrophobic faces in CNFs renders the dispersion polymer‐like rheological properties and good processability with tunable viscosity for 3D printing. A robust, degradable, and recyclable G‐CNF foam with designed shapes can be printed in a large scale, demonstrating higher mechanical strength (3.72 MPa versus 0.28 MPa in tensile strength and 2.34 MPa versus 1.11 MPa in compressive stiffness), better fire resistance, degradability, and recyclability than commercial polystyrene foam material. The demonstrated G‐CNF foam can potentially replace the commercial plastic foam materials, representing a sustainable solution toward white pollution. Abstract : A 3D graphite‐cellulose nanofibers hybrid aerogel is fabricated via 3D printing which demonstrates excellent mechanical strength with light weight, representing a new generation of cost‐effective, environmentally friendly, recyclable, and degradable foam material toward sustainable applications.